2013
DOI: 10.1002/ajoc.201300081
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Boletopsin 11 and 12, Antibiotics from the Traditionally Used Fungus Boletopsis sp.

Abstract: Magic mushrooms: The investigation of an edible Boletopsis mushroom that is used traditionally in Papua New Guinea as treatment for gastrointestinal complaints led to the discovery of two new heterocyclic p‐terphenyl ethers, boletopsin (1) and 12 (2), along with the known metabolites boletopsin 4 and 7 and cycloleucomelone. Evaluation of the antibiotic activity of the compounds isolated from this Boletopsis sp. supported the traditional medicinal use of the mushroom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…The purified synthetic compounds 1− 3 showed activity comparable to that of the natural isolates, 6 while the activity of 16 and 20 suggested that the 4′-OMe group is not crucial in the activity of the boletopsins.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The purified synthetic compounds 1− 3 showed activity comparable to that of the natural isolates, 6 while the activity of 16 and 20 suggested that the 4′-OMe group is not crucial in the activity of the boletopsins.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…The characteristic data for synthetic boletopsin 11 were identical with those of natural boletopsin 11. 6 The formation of boletopsin 7 (1) was achieved by the treatment of 20 with boron tribromide at −78°C, giving the tetrahydroxy pterphenyl in 68% yield (Scheme 6). The data for synthetic boletopsin 7 were identical with those of the natural boletopsin 7.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…used traditionally by the Kiovi Tribe of the Lufa District in the Eastern Highlands as a food source and as a treatment for gastrointestinal complaints. 1 It is widely accepted among natural product chemists that terrestrial fungi do not produce brominated metabolites, 2 but during our investigation of the chemistry of this fungus we discovered two polybrominated compounds, reported here as boletopsins 13 (1) and 14 (2) (Figure 1). We report here the isolation and definitive structural elucidation, through synthesis, of the first polybrominated metabolites, boletopsin 13 and boletopsin 14, to be isolated from a terrestrial fungus.…”
mentioning
confidence: 97%
“… Structural elucidation of the natural product was achieved using NMR and mass spectrometry, suggesting the connectivity and the relative stereochemistry of the densely substituted 1 H -cyclopenta­[ b ]­benzofuran. In the isolation report, it was hypothesized that suillusin ( 1 ) biosynthetically originates from polyporic acid, thus sharing a common metabolic precursor with the p -terphenyl natural product family (e.g., ganbajunin 8 ( 2 ) and boletopsin 11 ( 3 )). Notably, fungal metabolites that feature the densely functionalized 1 H -cyclo­penta­[ b ]­benzo­furan core are relatively atypical among other members of the arylpyruvic acid p -terphenyl family, raising questions surrounding suillusin’s biosynthetic origin.…”
mentioning
confidence: 99%